52nd IEEE Conference on Decision and Control 2013
DOI: 10.1109/cdc.2013.6759879
|View full text |Cite
|
Sign up to set email alerts
|

Network anomaly detection: A survey and comparative analysis of stochastic and deterministic methods

Abstract: Abstract-We present five methods to the problem of network anomaly detection. These methods cover most of the common techniques in the anomaly detection field, including Statistical Hypothesis Tests (SHT), Support Vector Machines (SVM) and clustering analysis. We evaluate all methods in a simulated network that consists of nominal data, three flowlevel anomalies and one packet-level attack. Through analyzing the results, we point out the advantages and disadvantages of each method and conclude that combining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Packet-based attack identification methods use packet header information, such as IP address and header size, to infer the degree of anomaly. Wang et al [5] used packet header information and correlation between the target IP address and port of edge routers for identification. LUCID [6] represented the packet header data sequence as an image and used CNN for feature learning.…”
Section: Packet-based Attack Identification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Packet-based attack identification methods use packet header information, such as IP address and header size, to infer the degree of anomaly. Wang et al [5] used packet header information and correlation between the target IP address and port of edge routers for identification. LUCID [6] represented the packet header data sequence as an image and used CNN for feature learning.…”
Section: Packet-based Attack Identification Methodsmentioning
confidence: 99%
“…To address the above problems, research in attack identification has evolved significantly over time, as shown in Figure 1. Early works [5,6] used plaintext information extracted from packet headers to make inferences about the degree of anomalies, such as IP address and packet header size, as shown in Figure 1a. However, these methods only rely on header information with a short length and single feature dimension, needing more analytical study of correlation features among packets from a holistic perspective, and the available plaintext information becomes more ambiguous.…”
Section: Introductionmentioning
confidence: 99%